2019
DOI: 10.1002/prot.25699
|View full text |Cite
|
Sign up to set email alerts
|

Side chain rotameric changes and backbone dynamics enable specific cladosporin binding in Plasmodium falciparum lysyl‐tRNA synthetase

Abstract: Cladosporin (CLD) is a fungal metabolite that kills the malaria parasite via inhibiting its cytoplasmic lysyl‐tRNA synthetase (KRS) and abrogating protein translation. Here we provide structural and drug selectivity analyses on CLD interacting residues in apo and holo KRSs from Plasmodium falciparum, Homo sapiens, Cryptosporidium parvum, and Mycobacterium ulcerans. We show that both gross and subtle alterations in protein backbone and sidechains drive the active site structural plasticity that allows integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The Plasmodium KRS (for cladosporin, CLD) and PRS (for halofuginone) are currently being studied as potential drug targets [19, 24, 5961]. We analysed CLD which, along with its analogs, is being investigated as an inhibitor of P. falciparum -KRS ( Pf -KRS) and of various other pathogen KRSs [21, 62]. Several amino acid residues in CLD binding pocket are highly conserved except at two positions near the ATP binding pocket and adjacent to CLD methyl moiety (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Plasmodium KRS (for cladosporin, CLD) and PRS (for halofuginone) are currently being studied as potential drug targets [19, 24, 5961]. We analysed CLD which, along with its analogs, is being investigated as an inhibitor of P. falciparum -KRS ( Pf -KRS) and of various other pathogen KRSs [21, 62]. Several amino acid residues in CLD binding pocket are highly conserved except at two positions near the ATP binding pocket and adjacent to CLD methyl moiety (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6b). It is noteworthy that biochemical analysis of recombinant KRSs has previously shown that CLD displays a nanomolar range potency of inhibition (IC50 ~ 40–90 nM) against Pf -KRS, which is ~ 500-fold higher when compared with Hs -KRS [20, 62, 63]. This suggests potential poor selectivity for P. tigris KRS due to the same bulkier residues (QT) at the CLD binding pocket in comparison to the smaller, more favourable residues (CS/VT) in Babesia spp.…”
Section: Resultsmentioning
confidence: 99%
“…It was noted that the isocoumarin moiety makes comparatively stronger H-bond with side chains of Glu325, Asn332 and Arg553 (Supporting Information Figure S4). [25,27] The THP moiety of cladosporin is stabilized by hydrophobic interactions with the side chains of Thr337, Glu494 and Asn497.…”
Section: Structural Comparison Of Atp and Cladosporin Bound Hskrsmentioning
confidence: 99%
“…Additionally, we recently extended the r.m.s.d.-r.m.s.d. /res analyses to another set of aaRS structures bound to ATP at 2.3 Å resolution and cladosporin at 2.1 Å resolution (Chhibber-Goel & Sharma, 2019). R.m.s.d.s for ATP-bound Homo sapiens lysyl-tRNA synthetase (HsKRS) structures remain below $1 Å and the maximum r.m.s.d.…”
Section: Heterogeneity Within Protomersmentioning
confidence: 99%